Upaya Meningkatkan Hasil Belajar Matematika Materi Rasio melalui Model Problem Based Learning pada Siswa Kelas VI SD - Nur Hadi; Supardi U. S (Lembaga Pengembangan Kinerja Dosen, 2025)
This class action research was carried out on grade VI students of SD N Sukamaju, Megamendung District, Bogor Regency, for the 2024/2025 Academic Year, to improve mathematics learning outcomes, especially in ratio materials. The Problem-Based learning (PBL) model is applied in two cycles, each of which includes planning, implementation, observation, and reflection. The results showed an increase in student enthusiasm from 35.00% in the initial condition to 60.00% in the first cycle and 75.00% in the second cycle. An increase was also seen in learning outcomes, which increased from 65.65% in cycle I to 91.30% in cycle II. Students' activity in understanding the concept of ratio increased from 60.00% in cycle I to 90.00% in cycle II, while learning satisfaction based on questionnaires increased from 72.50% to 92.50%. The teacher's ability to implement PBL also developed from a fairly good category with a score of 1.9 to very good with a score of 3.24 in the first cycle and 3.9 in the second cycle. The final evaluation showed an increase in student learning completeness from 35.00% in the initial condition to 60.00% in the first cycle and 95.00% in the second cycle, with the average class increasing from 57.50 to 70.00 in the first cycle and 81.75 in the second cycle. These findings indicate that the PBL approach effectively improves student engagement and learning outcomes in understanding the concept of ratios.